PENINGKATAN LITERASI EKONOMI PETANI HORTIKULTRA DALAM ANALISIS KELAYAKAN USAHATANI BERBAGAI KOMODITAS HORTIKULTURA DI KECAMATAN SUWAWA SELATAN - Arsyad, Karlena; Sirajuddin, Zulham; Amin, Nur Silfiah (Universitas Mataram, 2024)
Horticulture has great potential because compared to food crops, these plants can be harvested several times a year, making it a solution to improving people's welfare. The development of horticulture is expected to increase land productivity, encourage food diversification, and improve the economic welfare of farmers. However, obstacles in understanding horticultural farming analysis, especially in analyzing the profits and feasibility of farming, are obstacles in projecting the potential profits of horticulture as agricultural potential at the local level. KT Al-Hidayah faces one of the challenges in developing horticultural cultivation, namely a lack of understanding of farming analysis. So in-depth knowledge of this matter is needed in order to optimize strategies and decision making in farming. The methods implemented in this activity are training and mentoring. In training activities, the implementing team focuses on farming analysis and farmer group management. Then after the training activity, assistance is provided to optimize the results obtained in the training activity. There are still many participants who do not know about farming analysis before this activity is carried out. So that after training and mentoring, almost 100% of participants can understand farming analysis well and are willing to apply the knowledge gained to the business they run. So the expected output from this community service activity is that farmers can know and understand correctly how good farming analysis can be achieved, so that this can develop their farming business by obtaining the expected profits. Farming analysis training activities in order to optimize the dissemination of various types of horticulture farming provide benefits to horticultural farmers, where there is an increase in the ability to analyze farming based on post test results which show that 96.5% of participants are able to understand farming analysis well.